Study on the Binding Interaction of Three-finger Toxins From Cobras And Mangrove Catsnake Toward Nicotinic Acetylcholine Receptors: A Computational Approach - Nor Asyikin Zukifli; Muhamad Rusdi Ahmad Rusmili; Iekhsan Othman; Ahmad Khaldun Ismail; Janeyuth Chaisakul; Zalikha Ibrahim (IIUM Press, International Islamic University Malaysia, 2022)
Introduction: Snake venom is a combination of various proteins and peptides that cause diverse biological effects on multiple organ systems. In elapid venom, three-finger toxins are the most abundant type of toxin. Although toxins share similarities in their structure, they are known for their capability to cause a myriad of toxic actions such as neurotoxicity, cardiotoxicity, and cytotoxicity. Unfortunately, many of these toxins are not fully characterized especially on their binding affinity and selectivity towards receptors and their effect to the organ system. Materials and method: Therefore, this work was conducted to compare the binding properties of selected three-finger toxins (3FTxs) from cobras (Naja sumatrana and Naja kaouthia) and mangrove catsnake (Boiga dendrophila) towards human and bird nicotinic acetylcholine receptors (?3?2, ?4?2, ?7) using computational approaches. Results: The results show that all toxins bind to the orthosteric site, which is located outside the extracellular domain of ? subunit for all receptors in both species. Interaction between receptors and toxins occurs by the formation of hydrogen bond, ionic bond, and hydrophobic contact with important residues involved in their binding pocket. Conclusion: Based on the data, the toxins showed different binding affinities towards nicotinic acetylcholine receptors in different species. Differences in the binding affinity towards different species could have a significant impact on the functional characterization of venom caused by these toxins and toxins with nearly similar sequences.